Impact of diversity of Mycoplasma hyopneumoniae strains on lung lesions in slaughter pigs. (January 2018) - Michiels, Annelies; Vranckx, Katleen; Piepers, Sofie; Pozo Sacristán, Rubén; Arsenakis, Ioannis; Boyen, Filip; Haesebrouck, Freddy; Maes, Dominiek
Abstract The importance of diversity ofMycoplasma hyopneumoniae (M. hyopneumoniae ) strains is not yet fully known. This study investigated the genetic diversity ofM. hyopneumoniae strains in ten pig herds, and assessed associations between the presence of different strains ofM. hyopneumoniae and lung lesions at slaughter. Within each herd, three batches of slaughter pigs were investigated. At slaughter, from each batch, 20 post mortem bronchoalveolar lavage fluid samples were collected for multiple locus variable-number tandem repeat analysis (MLVA), and lung lesions (Mycoplasma -like lesions, fissures) were examined. Multivariable analyses including potential risk factors for respiratory disease were performed to assess associations between the number of different strains per batch (three categories: one strain, two–six strains, ≥seven strains), and the lung lesions as outcome variables. In total, 135 differentM. hyopneumoniae strains were found. The mean (min.–max.) number of different strains per batch were 7 (1–13). Batches with two–six strains or more than six strains had more severeMycoplasma -like lesions (P = 0.064 andP = 0.012, respectively), a higher prevalence of pneumonia [odds ratio (OR): 1.30, P = 0.33 and OR: 2.08, P = 0.012, respectively], and fissures (OR = 1.35, P = 0.094 and OR = 1.70, P = 0.007, respectively) compared to batches with only one strain. In conclusion, many differentM. hyopneumoniae strains were found, and batches of slaughter pigs with differentM. hyopneumoniae strains had a higher prevalence and severity ofMycoplasma -like lung lesions at slaughter, implying that reducing the number of different strains may lead to less lung lesions at slaughter and better respiratory health of the pigs.